Comparative Study of the Antiviral Activity of Acyl Derivatives of 2,2′-Anhydro-1-β-d-Arabinofuranosylcytosine and Other Nucleosides Against Encephalitis in Mice - Nishiyama, Shinya (1977)
Anti-deoxyribonucleic acid virus activities of 3′-O-acyl derivatives of 2,2′-anhydro-1-β-d-arabinofuranosyl cytosine (cyclo-C) and 1-β-d-arabinofuranosylcytosine (Ara-C) were evaluated by using an in vivo test system in mice. Among the derivatives tested, 3′-O-decanoyl cyclo-C hydrochloride was the most effective against herpes simplex virus-induced encephalitis in mice when the drug was administered directly into infected brains of mice (target-organ treatment). A comparative study of the treatment of herpetic encephalitis in mice with 3′O-decanoyl cyclo-C and other nucleosides, including Ara-C, 9-β-d-arabinofuranosyladenine (Ara-A), and 5-iodo-2′-deoxyrudine (IUdR), proved Ara-A to be more efficacious than the other nucleosides, followed by 3′-O-decanoyl cyclo-C, which was more active than Ara-C and IUdR. Administration of 3′-O-acyl cyclo-C's by intraperitoneal injection, however, failed to demonstrate activity against herpetic encephalitis in mice. The antivaccinial activity of 3′-O-decanoyl cyclo-C was also compared with that of other compounds against encephalitis and dermal tail lesions in mice caused by vaccinia virus infection. Interaperitoneally administered 3′-O-decanoyl cyclo-C and Ara-C also showed no significant activity against the diseases. Under these test conditions, N-methylisatin-β-thiosemicarbazone (Marboran) was the most active compound, followed by Ara-A.